Is the level of serum lactate dehydrogenase a potential biomarker for glucose monitoring with type 2 diabetes mellitus? - Hsieh, Yu-Shan; Yeh, Min-Chun; Lin, Yan-Yu; Weng, Shuen-Fu; Hsu, Chung-Huei; Huang, Chen-Ling; Lin, Yu-Pei; Han, A-Young (Frontiers in Endocrinology, 2022)
Type 2 diabetes mellitus (T2DM) is a metabolic disorder due to defects in insulin secretion or insulin resistance leading to the dysfunction and damage of various organs. To improve the clinical evaluation of short-term blood glycemic variability monitoring, it is critical to identify another blood cell status and nutritional status biomarker that is less susceptible to interference. This study identifies the significance of serum lactate dehydrogenase (LDH) level among T2DM patients treated in the outpatient clinics and investigates the relationships of LDH level with other variables. This study comprised 72 outpatients with T2DM over 20 years of age. Blood samples were collected, followed hematological analysis with serum glycated albumin (GA), LDH, fasting blood glucose, glycosylated hemoglobin, C-peptide, and insulin antibodies (insulin Ab). Serum LDH level was significantly correlated with GA (p < 0.001), C-peptide (p = 0.04) and insulin Ab (p = 0.03), and thyroid stimulating hormone (TSH) levels (p = 0.04). Hence, we performed a linear regression analysis of hematological markers, the GA (p < 0.001, r2 =0.45) and insulin Ab (p < 0.001, r2 =0.40) was significantly associated with LDH level. Followed we classified patients into low (< 200 U/L) and high (≥ 200 U/L) serum LDH level groups, respectively. GA (p < 0.001), C-peptide (p = 0.001), and TSH (p = 0.03) showed significantly difference in patients with high LDH levels compared with those in patients with low LDH levels. In conclusion, we suggested that LDH level was independent of long-term but associated with short-term blood glucose monitoring. The result indicates that changes in serum GA , induced the cell damage and serum level of LDH abnormally elevation may occur simultaneously when glycemic variability. Many biomarkers had been reported for observing the glucose variability in T2DM. However, the LDH could provide a more convenient and faster evaluation the glycemic variability in T2DM.